Aquatic Toxicology Notes: Diquat - P. Chris Wilson; Jun Wu (EDIS)
Diquat is applied directly to plants along ditch banks and within aquatic systems. It may also be applied to ponds, lakes, and drainage ditches to control algae and submersed aquatic weeds. This 7-page fact sheet introduces users of diquat to the physical, chemical, environmental, and ecological properties of this herbicidal active ingredient relative to the aquatic environment. Written by P. Chris Wilson and Jun Wu, and published by the UF Department of Soil and Water Science, October 2012.